Eupatorium odoratum-a Common Weed Found in the Teak Plantations of Kerala State - Moni, N. S.; George, M. P. (Indian Forester, 1959)
The weed Eupatorium odoratum believed to have been introduced recently into Kerala state has multiplied in such alarming proportions that the forests are fully invaded by this weed. It has cost enormous damage to teak plantations. During the last one decade it is believed to have damaged thousands of acres of teak plantations. Measures adopted for its eradication by the forest department proved to be ineffective and costly. It is even estimated that the weeding operation would cost Rs. 2 lakhs and expenditure is really prohibitive. Due to its slow. Decaying nature it has not appealed to the cultivators as a green manure. Even composting for oneyear shows that the stem of the plant still retains P2O5 and Potash (Phosphoric Acid and Potash). An acre of this weed Eupatorium will yield 25,000 lb. of green matter per cutting and it can be reasonably expected to give two cuttings in a year. The analysis of the dry matter as well as the ash show that it has immense potentialities as a source of plant food. A process has been developed by which these valuable plant foods can be manufactured in a convenient form under a cottage industry basis. An acre of Eupatorium odoratum can provide the following amounts of the different plant food constituents. Nitrogen - 200lb. Phosphoric acid - 100lb. Potash - 200lb. CaO - 125lb. It is hoped that the value of the fertilisers will be more than enough to provide for the cost of weeding. Another useful 1ine of investigation is the utility of Dicalcic phosphates, a product obtained from this plant, as a cattle feed. Further work is in progress.